Synthesis, characterization, immunological, and biological evaluation of several heterocyclic rings obtained from antipyrine derivatives - Kareem, Aseel Fadhil; Mahdi, Duha; Alhamdani, Hind Salih; Kadhum, Samah Ahmed (Pharmakeftiki, 2025)
The structures of newly synthesized heterocyclic compounds incorporating 4-aminoantipyrine (a key intermediate for the development of diverse derivatives) were elucidated through melting point analysis, Fourier-transform infrared spectroscopy (FTIR), and evaluation of physical properties. These compounds were subsequently tested for antibacterial activity against both Gram-positive and Gram-negative bacterial strains, specifically: Staphylococcus aureus and Streptococcus mutans (Gram-positive); Shigella flexneri and Pseudomonas aeruginosa (Gram-negative). Among heterocycles bearing three nitrogen atoms, antipyrine-based derivatives represent a widely studied structural class with significant relevance in academic research and medical applications. Although not naturally occurring, these compounds exhibit versatile utility across organic synthesis, chemical biology, polymer chemistry, supramolecular chemistry, and pharmaceutical development. Accordingly, the establishment of a straightforward and efficient synthetic route for antipyrine derivatives remains a priority. All tested compounds demonstrated notable antibacterial efficacy when benchmarked against conventional antibiotics. Moreover, in vivo studies revealed their capacity to induce pro-inflammatory cytokines such as interferon-gamma (IFN-γ), secreted by CD4⁺ T helper 1 (Th1) cells, thereby suggesting an immunomodulatory role.